О мифологических мотивах в былине “Добрыня и Настасья” - Yuyukin, Maxim Anatol’evich (Studia mythologica Slavica, 2020)
This article deals with mythological motifs reflected in the bylina “Dobrynya and Nastas’ya” discussed in comparison with the Baltic, South Slavic, and Ossetic epic texts.